2018
DOI: 10.1016/j.jbusres.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Is high recovery more effective than expected recovery in addressing service failure? — A moral judgment perspective

Abstract: In the context of two distinctive consumer categories and two different product settings this research examines the effects of recovery on recovery performance as a function of consumer moral judgment of service failure. The findings of two studies reveal that consumers' response to recovery anchors on the magnitude of recovery but these responses are adjusted according to consumers' moral judgment of service failure. Specifically, consumers react more positively toward expected recovery than high recovery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 62 publications
4
42
0
Order By: Relevance
“…Further, the complainant–recipient model provides no grounds for dissatisfied customers to detach from other additional detrimental activities, albeit prior failure‐recovery studies proposed the opposite (Ringberg et al, ; Schoefer & Diamantopoulos, ). The growing advent of social media has empowered customers' antagonistic stance (Chen et al, ; Maxham & Netemeyer, ; Weitzl & Hutzinger, ).…”
Section: Discussion: the Complainant–recipient Model Of Online Nwommentioning
confidence: 99%
See 3 more Smart Citations
“…Further, the complainant–recipient model provides no grounds for dissatisfied customers to detach from other additional detrimental activities, albeit prior failure‐recovery studies proposed the opposite (Ringberg et al, ; Schoefer & Diamantopoulos, ). The growing advent of social media has empowered customers' antagonistic stance (Chen et al, ; Maxham & Netemeyer, ; Weitzl & Hutzinger, ).…”
Section: Discussion: the Complainant–recipient Model Of Online Nwommentioning
confidence: 99%
“…The vindictive behavior of frustrated customers with online nWOM is associated with purchase reduction and decrease in trust, whereas paying others to spread nWOM, self‐usage of multiple platforms to spread nWOM and switching behavior are post‐recovery activities of aggressive customers. Although post‐recovery activities have been proposed to have a negative impact on the provider, past research yields a gap between the expected and experienced recovery (Chen et al, ).…”
Section: Discussion: the Complainant–recipient Model Of Online Nwommentioning
confidence: 99%
See 2 more Smart Citations
“…Smith et al, 1999). Recently, Chen et al (2018) demonstrated online customers' perception of compensation in terms of moral judgement. They report that compensation gets acknowledged in a moral discourse, revealing that customers who perceive online failure as a morally affecting act perceive compensation as the strategy used for 'punishing the business for unintended outcomes' (p. 3).…”
Section: Introductionmentioning
confidence: 99%